On the Issue of Constitutional Law Realization Regarding Favorable Environment and Radiation Security - A. M. Shafikov (Сибирское юридическое обозрение, 2014)
The article deals with the main realization problems of citizen’s rights of favorable environment and radiation security. The author comes to the conclusion about the necessity of target programming method employment in the solution of the problems revealed.